Buildings that changed the world - Reichold, Klaus; Graf, Bernhard (Munich ; New York : Prestel, 2004)
A photographic journey though five thousand years of architecture, examining cultural and historic details associated with some of the world's most significant buildings and structures.
First published: 1999.
Includes bibliographical references (p. 186-190).
Books for the Teen Age (NYPL), April 2001
Adult
Keywords: Architecture -- History; Buildings -- History